The Influence of Distributive Justice, Procedural Justice, and Perceived Organizational Support on Organizational Citizenship Behavior (OCB): The Mediating Role of Employee Engagement and Moderating Transformational Leadership - Nurul Hasanah; Gusti Meinar Girda Ariani; Farida Yulianti; Syahrani Syahrani; Abdul Halik (Business Management, 2025)
This research investigates how distributive justice, procedural justice, and perceived organizational support influence Organizational Citizenship Behavior (OCB), with employee engagement serving as a mediating factor and transformational leadership acting as a moderating element. The study targeted employees working at the Secretariat of Banjarmasin City Government and utilized a quantitative research design. Data were gathered using a purposive sampling technique through questionnaires administered to 150 participants. The analysis was carried out using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach.The findings reveal that distributive justice, procedural justice, and organizational support perceptions significantly enhance both employee engagement and OCB. Additionally, employee engagement plays a crucial mediating role in the connection between these independent variables and OCB. Transformational leadership further moderates this relationship, amplifying the positive impact of employee engagement on OCB. These results highlight the importance of fair treatment and supportive work environments in fostering OCB, particularly when guided by transformational leadership.This study provides practical implications for public sector management to pay more attention to justice and support aspects as strategic efforts to improve employees’ extra-role performance through OCB.